The trench : life and death on the Western front 1914-1918 - Yorke, Trevor (Countryside Books, 2014)
The horrors of World War I scarred an entire generation at the beginning of the twentieth century. Now, one hundred years later, we are asked to reflect upon it and remember what a disastrous episode of history it was. This book offers a brief, straightforward, illustrated history of World War I. In particular, it explains the trenches and what it was like to live and fight in them. Using his own diagrams, illustrations, and maps, author Trevor Yorke explains the architecture of the trenches, with their command posts, sally points, tunnels, machine gun nests, duck boards, and sleeping billets. There are chapters to explain tactics, weaponry, and daily life. There are special features on the introduction of new weapons of war, such as tanks, early aeroplanes, and the first use of poison gas. These can bring home to us a real understanding of the unique inhumanity of the war, and why the dates 1914-1918 require all generations of today to remember and learn from them. As Michael Morpurgo, author of War Horse, says in his Foreword: 'As we begin to mark the centenary of the First World War, we should honour those who died, most certainly, and gratefully too, but we should never glorify. During these next four years of commemoration we should read the poems, the stories, the history, the diaries, visit the cemeteries German cemeteries as well as ours they were all sons and brothers and lovers and husbands and fathers too.'